The role of African spirituality in conflict management with reference to the Akamba of Utithini village in Machakos county of Kenya. - Mwania, Patrick (Nairobi : Maryknoll Institute of African Studies, 2017)
In partial fulfillment of the requirement for the degree of Masters of Arts Maryknoll Institute of African studies of Saint Mary's university Nairobi and Winona, Minesota.
Keywords: Akamba (African people) -- social aspects -- Kenya; Research -- Thesis